Adaptation of plants for the distribution of seeds - Thompson, Barton (My University, 1900)
Introduction: The forms that plants take and the methods they adopt to distribute their seeds so as to be of most benefit to the plant, and to insure their continuance, are innumerable. The modes of distribution; though in many cases they merge into each other, can be classified for convenience into five main groups, vig: 1. By tension and turgor—sling fruits. 2. Catapult fruits. 3. Distributed by wind. 4. Distributed by animals. 5. Distributed by water. We will now take these up in regular order, and will give, as far as practicable, illustrations, showing the principal characteristic types of distribution of each of the subheads of the groups
Citation: Thompson, Barton. Adaptation of plants for the distribution of seeds. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Horticulture; Seed Distribution; Seeds; Theses; Manuscripts (documents)